Mechanisms Underpinning the Link between Emotion, Physical Health and Longevity - Andrew H. Kemp (Frontiers Research Topics, 2017)
The 1990's was designated as 'the decade of the brain' and now, common mental disorders are described as 'brain disorders'. Yet intense research interest on the brain has largely side-lined the body as a passive observer, disconnecting mental from physical health and contributing to further societal stigma on the nature of psychiatric illness and mental distress. The biopsychosocial pathway to premature mortality or longevity is a complex one, involving a host of closely intertwined mechanisms and moderating factors, some of which are investigated in this special issue. All the articles published here provide new insights into the pathways linking emotion, physical health and longevity, highlighting the tight linkage between mind, brain and body.